The use and teaching of discourse markers in Hong Kong: students' production and teachers' perspectives - Fung, Loretta Po-yin (2003)
The present study attempts to investigate discourse markers from a functional and attitudinal perspective. Based on the pedagogical sub-corpus from CANCODE and the audio-recordings of class discussion of 49 secondary pupils in Hong Kong, Part I explores the roles discourse markers play in spoken discourse on a contextual basis and compares the different use of discourse markers by British and Hong Kong speakers of English using quantitative and qualitative methods. Discourse markers are found to serve as useful contextual coordinates to structure and organise speech on interpersonal (marking shared knowledge, attitudes and responses), referential (indicating textual relationships such as cause, contrast, coordination, digression, consequence, etc. ), structural (summarising opinions, marking sequence, opening and closing of topics, transition and continuation of topics) and cognitive (denoting hesitation and thinking process, marking reformulation, self- correction or elaboration, and assessing the listener's knowledge about the utterances) realms, bearing a probabilistic relationship with the various role(s) on a multifunctional dimension in pedagogic discourse. Functionally, non-native speakers are found to display a highly restricted use of discourse markers, especially those interactive ones (e.g. initial and, yeah, you know, ), whereas native speakers tend to use discourse markers more for a variety of pragmatic functions. Part II contains a questionnaire survey (N=132) and an interview study (N=3) of Hong Kong teachers. Reliability test and factor analysis were conducted In the quantitative part. The results indicate a very positive perception of the pragmatic and pedagogic value of discourse markers by the teachers where students at intermediate-advanced level are challenged to acquire them for both receptive and productive purposes. The findings also reveal teachers' preference to conform to an exonormative speaking model and their less favourable attitude towards the Hong Kong variety. They are not certain regarding the representation of discourse markers in the existing teaching materials and their actual teaching. The study has implications for second language teaching in five areas: (1) introducing discourse markers as a communication strategy; (2) developing learners' linguistic awareness of discourse markers as an instructional strategy; (3) utilising corpus-based research for materials development; (4) equipping teachers with a World English perspective; and (5) creating space for the development of Hong Kong English to prepare learners to communicate in a dynamic linguistic world.